Elastic strain associated with irradiation-induced defects in self-ion irradiated tungsten - He, G; Yu, H; Karamched, PS; Liu, J; Hofmann, F (Elsevier, 2023)
Elastic interactions play an important role in controlling irradiation damage evolution, but remain largely unexplored experimentally. Using transmission electron microscopy (TEM) and high-resolution on-axis transmission Kikuchi diffraction (HR-TKD), we correlate the evolution of irradiation-induced damage structures and the associated lattice strains in self-ion irradiated pure tungsten. TEM reveals different dislocation loop structures as a function of sample thickness, suggesting that free surfaces limit the formation of extended defect structures that are found in thicker samples. HR-TKD strain analysis shows the formation of crystallographically-orientated long-range strain fluctuations above 0.01 dpa and a decrease of total elastic energy above 0.1 dpa.